2020
DOI: 10.1186/s12864-020-06870-x
|View full text |Cite
|
Sign up to set email alerts
|

Shedding light on cashmere goat hair follicle biology: from morphology analyses to transcriptomic landascape

Abstract: Background: Cashmere goat is known for its precious undercoat. Being photoperiod-dictated, cashmere growth has been studied focusing mainly on hair follicle cycle phases (anagen, catagen and telogen). An accurate molecular knowledge of the goat hair follicle cycle, disentangling gene expression changes during phases and recognizing timing boundaries, could be useful to improve cashmere goat management and ultimately cashmere production. Results: To better describe goat's hair follicle transcriptome we applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Following activation of membrane-bound adenylyl cyclase, ATP is converted to cAMP. Adenylate cyclase 1 (Adcy1) is the most upregulated gene in the oestrogen pathway during catagen [ 40 ]. While ADCY2 is another member of the adenylyl cyclase family.…”
Section: Discussionmentioning
confidence: 99%
“…Following activation of membrane-bound adenylyl cyclase, ATP is converted to cAMP. Adenylate cyclase 1 (Adcy1) is the most upregulated gene in the oestrogen pathway during catagen [ 40 ]. While ADCY2 is another member of the adenylyl cyclase family.…”
Section: Discussionmentioning
confidence: 99%
“…Our enrichment results are consistent with a previous study where the oxidative phosphorylation pathway was reported to be related to hair follicle cycling [ 34 ]. The thermogenesis pathway was another enriched pathway in our study, which was unusual of the hair follicle cycle activities, underlining the relationship between environmental temperature and hair growth [ 38 ]. The present study confirmed the abnormal expression of several pathways related to hair growth.…”
Section: Discussionmentioning
confidence: 99%
“…This hair shaft central part possesses the most complicated spectra of keratins, including keratins of ORS, IRS, hair shaft cuticle, and cortex ( Figure 2 ) [ 168 ]. Several noncanonical skin or hair keratins could be identified in hair follicles of different mammalian taxons, in particular, including a unique mammal-specific splice variant of keratin 80 in humans [ 171 ] or mucosa-related keratin 4 and 13 in cashmere goats [ 172 ]. Hair and nails, as well as other hard keratinized mammalian skin derivatives such as horns and hoofs, are examples of highly restricted unique keratin expression areas.…”
Section: Keratin Expression Patternmentioning
confidence: 99%